INVESTIGATING THE EFFECT OF AN UNDERDEVELOPED FINANCIAL SECTOR ON NON-OIL EXPORT IN NIGERIA - Ayoade Ogunjumo, Rotimi (Economic Annals, 2024)
Several policies have been implemented in Nigeria to shift the export trade from oil to non-oil goods; yet the share of non-oil export in total exports remains very small compared to oil export, which may be due to the low level of financial sector development in the country. Unlike previous studies on Nigeria that focused exclusively on financial sector development and aggregate export (combined exports of oil and non-oil goods), this study concentrates on financial sector development and non-oil export using an autoregressive distributed lag technique, the dynamic ordinary least squares technique, and the non-linear autoregressive distributed lag technique over the period 1986–2020. The empirical results showed that the relationship between financial sector development and non-oil export is linear. Results also showed that, in the short term, the country’s level of financial sector development worsens exports of non-oil products. However, in the long term, there is no connection between non-oil export and financial sector development, which challenges the theoretical view that trade and financial sector development are linked at any given time period. The study recommends that the government and policymakers in Nigeria should make sure that the financial sector is sufficiently developed, otherwise the goal to diversify the export base may not be achieved.